Solar‐Driven Hydrogen Peroxide Production via BiVO4‐Based Photocatalysts - Hui Ling Tan; Casandra Hui Teng Chai; Jerry Zhi Xiong Heng; Quyen Vu Thi; Xuelian Wu; Yun Hau Ng; Enyi Ye (Advanced Science)
Abstract Solar hydrogen peroxide (H2O2) production has garnered increased research interest owing to its safety, cost‐effectiveness, environmental friendliness, and sustainability. The synthesis of H2O2 relies mainly on renewable resources such as water, oxygen, and solar energy, resulting in minimal waste. Bismuth vanadate (BiVO4) stands out among various oxide semiconductors for selective H2O2 production under visible light via direct two‐electron oxygen reduction reaction (ORR) and two‐electron water oxidation reaction (WOR) pathways. Significant advancements have been achieved using BiVO4‐based materials in solar H2O2 production over the last decade. This review explores advancements in BiVO4‐based photocatalysts for H2O2 production, focusing on photocatalytic powder suspension (PS) and photoelectrochemical (PEC) systems, representing the main approaches for heterogenous artificial photosynthesis. An overview of fundamental principles, performance assessment methodologies, photocatalyst and photoelectrode development, and optimization of reaction conditions is provided. While diverse strategies, such as heterojunction, doping, crystal facet engineering, cocatalyst loading, and surface passivation, have proven effective in enhancing H2O2 generation, this review offers insights into their similar and distinct implementations within the PS and PEC systems. The challenges and future prospects in this field are also discussed to facilitate the rational design of high‐performing BiVO4‐based photocatalysts and photoelectrodes for H2O2 generation under visible light.